Climate imaginaries and the mattering of the medium. Issue 137 (December 2022) - Davoudi, Simin; Machen, Ruth
Highlights: Imaginaries influence climate knowledge and action and fix or unsettle visions of the future. The imbrication of discourse and materiality is key to understanding the concept of imaginaries. The medium through which imaginaries are produced and circulated matter. Different mediums offer different affordances and constraints in shaping climate imaginaries. Attending to the role of mediums in climate imaginaries informs environmental governance debates. Abstract: Imaginaries are increasingly recognised as influential in shaping climate knowledge and action and in fixing or unsettling particular visions of the future. Whilst the imbrication of discourse and materiality is key to the distinctiveness of the concept of imaginaries, attention has tended to focus on their symbolic and discursive aspects, overlooking the role of the material dimension. In this paper we seek to bring back the material into thinking about imaginaries by critically examining the relationship between climate imaginarie s and the mediums through which they are produced and circulated. We argue that the medium is an active constituent of the productive work that imaginaries do. To construct this argument, we first distinguish the imaginary from associated debates around images and imagination, highlighting its theoretical utility in rebutting modernist dualism between the material and the ideal. Second, we propose the concept of 'medium' as a way of foregrounding the material dimensions of the imaginary without re-inscribing the binary between the virtual and the material or imputing an overly agentic or predetermined role for the latter. Deploying a co-productionist approach and foregrounding process of mediation, we signal the affordances and constraints of mediums in shaping climate imaginaries. Third, we provide a comparison between climate poetry and computerised climate scenario models to examine how each offers different potentials and limitations to the imaginaries that they co-produce, and how the medium matters to the production and circulation of climate change imaginaries. We conclude by outlining an emerging research agenda and highlighting some of the implications of attending to the role of the medium in climate change imaginaries for contemporary environmental governance debates.